Experimental Study on the Performance and Microstructure of Cementitious Materials Made with Dune Sand - Chaohua Jiang; Xiaobin Zhou; Guilan Tao; Da Chen (Advances in Materials Science and Engineering)
This paper presents the results of an investigation on the utilization of dune sand from waterway regulation engineering as the main raw materials to produce cementitious materials. The mechanical and durability properties of the cementitious materials were studied. Furthermore, a scanning electron microscope (SEM) and mercury intrusion porosimeter (MIP) were used to identify the microstructure of the specimens. The results show that the compressive and splitting tensile strength of cementitious materials can be improved due to the addition of ground granulated blast-furnace slag (GGBS) which mainly attributes to a better grain size distribution and pozzolanic effect compared to the specimen added cement alone. The specimen with the addition of suitable cement, GGBS, and gypsum shows low dry shrinkage and excellent abrasion resistance. Correspondingly the specimens present a lower porosity and total volume of pores at different curing ages. The SEM observation indicates that there are quite a lot of hydrate products such as calcium silicate hydrate gel in the matrix which verifies the formation of cementitious compounds. The results obtained suggest that there is potential in manufacturing cementitious material with dune sand in substitution of ordinary concrete to use in hydraulic engineering.